Study on antioxidant activity and HIV-1 integrase inhibitory effect of smilax corbularia kunth - Rapiah Kejik (Prince of Songkla University, 2008)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University